Sierra Leone : : Visit of Mr. H. Vischer to Sierra Leone - Vischer, Hanns; Great Britain Colonial Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1933)
Typescript and ms. memoranda relating to Colonial Office arrangements for the visit to Sierra Leone of Hanns Vischer in Apr.-May 1933. The documents are chiefly concerned with the reimbursement of Vischer's expenses, but Vischer's report on education in Sierra Leone is also included